Review of Determinants of Nonmedical Caesarean Section in Indonesia: A Systematic Review - Nurfianto, Sigit; Suhanda, Rachmad; Yuarta, Ferina Agustia; Refani, Priska; Sembiring, Thyrister Nina Asarya; Mellazulfa, Dhea Sofiana; Laurentina, Yoriko; Yeni, Yeni (Jurnal Kedokteran Brawijaya, 2024)
Caesarean section (C-section) delivery has increased worldwide. The number of deliveries using the C-section procedure at the age of 10–54 years in Indonesia reached up to 17.6% of the total number of deliveries, due to the presence of medical and nonmedical indications. This study aims to analyze about nonmedical indications of C-section. This study uses a systematic review method. The inclusion criteria for the investigated studies were articles published in 2011–2021, written in English or Bahasa Indonesia, observational studies with case control or cohort as the design, and available to be downloaded in full text. In total, 12 articles were included in this systematic review. The nonmedical factors that influence the C-section procedure are antenatal care, the mother's level of education, residency, health insurance, socio-economics, occupation, previous birth histories, the mother's demand, the family's support and decision-making, and doctor's referral. The government, through the help of health practitioners, needs to increase the education to pregnant women and their families regarding the advantages and disadvantages of their preferred delivery methods.